UI/UX Development for Tour Ticketing on Pari Island using User Centered Design - Hudzafah, Abdullah; Pratiwi, Dian; Sari, Syandra (Intelmatics, 2025)
UI/UX Development of UCD-Based Tourism Tour Ticketing on Pari Island, which currently feels like the method of ordering tourism services on Pari Island is still too conventional, especially in the tourism sector. In fact, purchasing tourism tour tickets with methods that follow technological developments greatly influences efficiency in handling the surge of tourists coming to Pari Island, especially on weekends and other holidays. On Pari Island, purchasing tickets for tourism such as homestays, catering, snorkeling equipment rentals, bicycles, and motorbikes is still considered conventional where tourists who come to Pari Island must look for homestays and book tickets directly on the spot, in this study an application was created with a simple and attractive ticket purchasing concept (E-Ticket) which aims to improve the UCD-based tourism tour ticket ordering system on Pari Island.